To the Question about the Definition and the Essence of Administrative Activities in the Field of Environmental Protection and Natural Resource Management - Louise Siradzheddinovna Gamidullaeva (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article is devoted to definition of the definition of «administrative activities in the field of environmental protection and natural resource management» as the activities of the Executive authorities, their structural units and officials responsible for state administration in this area.